ANALISIS STRATEGI HOME INDUSTRI PENGRAJIN KAIN TAPIS DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI KELUARGA DI KELURAHAN KOMERING PUTIH LAMPUNG TENGAH - Tati Santia; Nedi Hendri; Ana Septiani (Universitas Muhammadiyah Metro, 2021)
This study aims to determine the Analysis of Home Industry Strategies for Tapis Fabric Craftsmen in Improving Family Economic Welfare in Komering Putih Village, Central Lampung. This study uses qualitative research. Data obtained from the results of interviews and documentation observations. The technique used is data analysis in three steps, namely, data collection, data reduction, and data presentation. The results of this study indicate that the strategy in the home industry of filter cloth craftsmen uses a marketing strategy with sales through offline and online media. The income in the home industry of this filter cloth craftsman continues to increase every month because orders for filter cloth always increase.